Genotype x environment interactions and stability analysis for root yield and quality traits in sugarbeet (Beta vulgaris L.) - Sanghera, Gulzar S.; Thind, K.S.; Singh, Navdeep; Singh, Rupinder Pal; Tyagi, V. (Annals of Agricultural Research, 2017)
Five sugarbeet genotypes were tested across nine environments (three dates of sowing; threelocations) during Rabi 2014-15 to assess the magnitude of genotype × environment interactions andstability for root yield and quality traits in sugarbeet. Pooled analysis of variance showed highlysignificant G × E interactions for characters like root length, root fresh weight, leaf fresh weight,whole plant weight, sucrose percentage and brix percentage. The environment and genotype ×environment (E + G × E) component was highly significant for root length, root fresh weight, rootdry weight, whole plant weight, root yield and sugar yield. Stability parameters viz., meanperformance over environments (μ), the linear regession (bi) and deviation from regression (S2di)were measured for root yield and quality parameters which revealed that Magnolia and Cauverygenotypes exhibited higher root yield (80.7 and 78.8 t/ha) and below average stability (bi < 1.0).Calixta genotype recorded highest sucrose (15.3 %) and regression coefficient more than unity (bi >1.0) coupled with significant regresson deviation. Magnolia and Cauvery exhibited higher sugaryield than mean yield and below average stability, but their performance was unpredictable.Genotypes that showed stability but were poor in mean performance can be involved in crosseswith agronomically desirable genotypes for respective characters, in a compensating manner inorder to give constant performance of the trait.